A survey on students’ attitudes to deductive and inductive approaches to teaching English grammar for grade 11th at Bac Kan Gifted High School - Trịnh, Thanh Huyền (2016)
Investigatingkey features of deductive and inductive approaches for deeper understanding. Designingstudents survey questionnaires and questions for semi - structured interviews. Observing teachers teachingthe two different approaches. Askingstudentsto do thesurvey questionnaires. Inviting some students to take part in semi –structured interviews. Collecting and analyzing the data collected